Is Omicron a Tsunami? What should be the strategy to prevent the loss? - Mulazim Hussain Bukhari (Journal of the Pakistan Medical Association, 2022)
The COVID-19 pandemic began in December 2019 with the 5th wave setting in from January 2022. Every wave was due to the emergence of a new variant of the virus. The first wave was caused by the Wuhan Virus from 26th February- September 2020, second wave lasted from 28th Oct 2020 to February 2021 whereas the third wave or UK variant emerged from our neighbouring country India. Corona first and second wave in Pakistan, and strategies The 1st and 2nd waves were associated with a low death rate. It was well controlled due to being timely managed by the Government. It was short lived as the case and death rates began to recede rapidly after peaking. The management policies of smart and partial lockdowns proved successful by curbing the transmission of the disease. The same strategies were adopted in the second wave. The first wave claimed 6795 lives, infected 332,186, left behind 632 on ventilators. During the 2nd wave, there were 579,973 infected and 12,860 died till 28th February 2021. Continues...